Kajian Pola Operasi MRT Jakarta Berdasarkan Okupansi Penumpang: Studi Kasus di Stasiun Lebak Bulus-Stasiun Bundaran HI - Alwahdi, Mahyuddin Hizbulloh; Kurniawan, Safrudin; Andana, Galang Febry (Journal of Engineering Education and Pedagogy, 2025)
The Jakarta Mass Rapid Transit (MRT) system is a rail-based public transportation network developed to address traffic congestion and overcrowding in the Greater Jakarta area. As the city's population continues to grow, public mobility is expected to increase significantly. This study aims to propose an operational pattern for PT MRT Jakarta in the year 2028, based on projected passenger demand. The research utilizes secondary data obtained from PT MRT Jakarta, including the MRT Jakarta feasibility study, passenger volume data, rolling stock information, and the existing Train Operation Schedule. Based on the analysis of travel demand, the minimum headway during peak hours is determined to be 3.5 minutes. The rolling stock requirement analysis indicates the need for 25 trainsets, each comprising 6 cars. Of these, 22 trainsets will be operated during peak hours, while 3 trainsets will be reserved for backup and maintenance at the MRT Jakarta depot. Furthermore, the frequency analysis estimates a total of 34 train trips per hour.